A modified oil lubrication system with flow control to reduce crankshaft bearing friction in a litre 4 cylinder diesel engine - Shayler, Paul J.; Cheng, Li; Li, Qile; Wahab, Emad (2016)
The oil distribution system of an automotive light duty engine typically has an oil pump mechanically driven through the front-endancillaries-drive or directly off the crankshaft. Delivery pressure is regulated by a relief valve to provide an oil gallery pressure of typically 3 to 4 bar absolute at fully-warm engine running conditions. Electrification of the oil pump drive is one way to decouple pump delivery from engine speed, but this does not alter the flow distribution between parts of the engine requiring lubrication. Here, the behaviour and benefits of a system with an electrically driven, fixed displacement pump and a distributor providing control over flow to crankshaft main bearings and big end bearings is examined. The aim has been to demonstrate that by controlling flow to these bearings, without changing flow to other parts of the engine, significant reductions in engine friction can be achieved. The study has been conducted on a 1.5litre, 4 cylinder turbocharged diesel engine. By reducing the feed pressure to the bearings from a baseline pressure of 3bar absolute to 1.5 bar absolute, reductions in engine rubbing friction mean effective pressure of up to 14% has been achieved at light load. Similar reductions in friction were recorded across a speed range of 1000-2000 rev/min and net indicated mean effective pressures up to 3.5 bar. The ranges were conservatively limited to protect against bearing damage. The paper reports details of the oil system modifications and the test results. The fuel economy benefit due solely to the friction reduction, not including any benefit from a reduction in oil pump work, is around 1½ % over the New European Drive Cycle (NEDC). The reduction in friction is demonstrably significant and represents an area with great potential to improve engine efficiency.